2005
DOI: 10.1128/jb.187.15.5166-5178.2005
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilisPhosphorylated PhoP: Direct Activation of the EσA- and Repression of the EσE-ResponsivephoB-PS+VPromoters during Pho Response

Abstract: The phoB gene of Bacillus subtilis encodes an alkaline phosphatase (PhoB, formerly alkaline phosphatase III) that is expressed from separate promoters during phosphate deprivation in a PhoP-PhoR-dependent manner and at stage two of sporulation under phosphate-sufficient conditions independent of PhoP-PhoR. Isogenic strains containing either the complete phoB promoter or individual phoB promoter fusions were used to assess expression from each promoter under both induction conditions. The phoB promoter responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…When additional PhoP-PhoR is not required, repression of P A6 by CcpA is not only energy efficient, it also avoids placing the cells at a selective disadvantage as has been observed when cellular concentrations of PhoP were increased inappropriately by expression from multicopy plasmids (34,42) or in spo0 mutants (23). The poor growth phenotype and/or rapid accumulation of spontaneous phoP or phoR mutations in cells overexpressing phoPR or phoP may be the result of inappropriate gene activation or inhibition by higher concentrations of PhoP or PhoPϳP, respectively, as observed in vitro (1).…”
Section: Discussionmentioning
confidence: 99%
“…When additional PhoP-PhoR is not required, repression of P A6 by CcpA is not only energy efficient, it also avoids placing the cells at a selective disadvantage as has been observed when cellular concentrations of PhoP were increased inappropriately by expression from multicopy plasmids (34,42) or in spo0 mutants (23). The poor growth phenotype and/or rapid accumulation of spontaneous phoP or phoR mutations in cells overexpressing phoPR or phoP may be the result of inappropriate gene activation or inhibition by higher concentrations of PhoP or PhoPϳP, respectively, as observed in vitro (1).…”
Section: Discussionmentioning
confidence: 99%
“…Further, not all APase expression in B. subtilis is PhoPϳP activated. phoB (formerly phoAIII) encoding APase B (formerly APase III) (5, 9) is expressed from two differentially regulated promoters, P S (E E -responsive promoter) and P v (E A -responsive promoter), which are PhoPϳP repressed and activated during PSI, respectively (2,5,9). The study by Caldwell et al (7) found a 9.3-fold increase in phoB expression in an scoC mutant compared to the WT strain at the last time point assayed (310 min after inoculation), an increase which represented the greatest fold increase in a group of sporulation genes dependent on Spo0A and F .…”
Section: Discussionmentioning
confidence: 99%
“…Which of these phosphatases gets expressed is dependent on the physiological conditions. Their cellular localization varies from secreted to membrane-associated, and it has been shown that the main members of this family, PhoA and PhoB, can complement each other (18,19). Although it has been proposed that the main biological function of the Pho enzymes is the provision of phosphate during phosphate starvation and that phoB expression is accordingly controlled, we were able to purify substantial amounts of PhoB from B. subtilis cells grown in rich medium, and therefore, we assume that PhoB is among the most abundant phosphatases even under those conditions.…”
Section: Identification and Characterization Of A Polyprenylglyceryl mentioning
confidence: 99%